Blood pressure studies in children : report of a WHO study group, meeting held in Geneva from 3 to 5 November 1983 - WHO Study Group on Blood Pressure Studies in Children; World Health Organization (Geneva : World Health Organization, 1985)
Evaluates the methodology and findings of blood pressure studies in children in an effort to clarify the early etiology of hypertension and suggest methods of primary prevention. The report opens with a critique of the different study designs and measurement procedures used to investigate the determinants of blood pressure level and change in childhood. The second section evaluates the results of epidemiological studies of blood pressure in infants, children and adolescents. Discussion centres on the determinants of change in blood pressure, the stability of blood pressure rank, and the prediction of future hypertension. The final section, devoted to primary prevention, summarizes what scientific evidence has to say about the feasibility of both community approaches and approaches aimed at recognizing and reaching children at particular risk.
Introduction -- 1. Background and rationale -- 2. Methods of studying blood pressure in childhood -- 3. Epidemiology of blood pressure in childhood -- 4. Primary prevention of hypertension -- 5. Conclusions and recommendations -- Acknowledgements -- References
Keywords: Blood Pressure Determination; Blood Pressure; Hypertension; Blood pressure in Childhood